A Review on The Second Edition of Farsi Biyamuzim - Esmat Khoeini; Mohammad Parsanasab; Naser Kermani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Despite the variety of electronic resources, textbooks continue to be the main medium of language teaching. Thus, criticizing them can improve the quality of education. This paper reviews the 1st volume of the 2nd Edition of “Farsi Biamuzim”, based on a set of standards and criteria for evaluating academic textbooks. Among the five criticism criteria of structure, content, language, method, and society and culture, the advantages of this work can be found in the general way of teaching the alphabet, providing innovative exercises, selecting practical topics, and designing useful topics in the content of lessons. Its disadvantages can be attributed to the structural inconsistency of the book in the instruction of letters and grammatical materials and the lack of a list of sources and a defect in its list of contents.